The public library and its control - Corbett, Edmund V. (London : Library Association (Association of Assistant Librarians), 1966)
This would be useful to students of librarianship studying for Library Association's examinations.
Includes index.
Includes bibliographical references: p. 141.
kjo 18/01/2019
Loans
Keywords: Public libraries